Murichromolaenicola thailandensis sp. nov. (Phaeosphaeriaceae, Dothideomycetes) from Chromolaena odorata (Asteraceae) in northern Thailand - Htet, Zin Hnin; Tibpromma, Saowaluck; Mapook, Ausana; Chethana, K.w. Thilini; Hyde, Kevin D. (Phytotaxa, 2023)
In this study, a saprobic species of Murichromolaenicola (Phaeosphaeriaceae, Dothideomycetes) was collected from dead stems of Chromolaena odorata in northern Thailand. It is introduced as a new species Murichromolaenicola thailandensis sp. nov. based on morphology and multigene phylogeny of combined LSU, SSU, ITS, tef1-α, and rpb2 sequence data. Murichromolaenicola thailandensis is similar to other Murichromolaenicola species by having muriform spores but can be differentiated by its smaller conidia with a gelatinous cap and the number of septa on conidia. Here, we present a detailed description, illustrations and antibacterial potential of this new species. Our findings contribute to the expanding knowledge of fungal diversity in Thailand and highlight the importance of utilizing molecular approaches to accurately identify and classify fungi in Ascomycota.